Implementation of the Concept of Multiple Intelligences Learning in an Islamic Perspective at Bayt Al-Hikmah Junior High School Pasuruan Islamic Boarding School (SBP) - Muhammad Munzaini; Sugiyo Sugiyo; Dardiri Hasyim (Publikasi Indonesia, 2022)
This study aims to determine the implementation model of the learning concept multiple intelligences in an Islamic perspective at SMP Bayt al-Hikmah Pasuran Islamic Boarding School (SBP). The type of research used is a qualitative approach descriptive. Data collection was carried out through in-depth interviews, participatory observation, and a review of documents. Data that has been collected were analyzed using qualitative data analysis techniques. The conclusions of this study are: (1) The theory of multiple intelligences can be used as a bridge to transfer a concept of knowledge that can be digested easily easier. The proof is that it can increase interest, talent. (2) Student input; by continuing to hold tests to find out the child's basic abilities about Pesantren and knowing that children are not children who have needs especially because this institution has not been able to prepare the facilities. Whereas the amount received is in accordance with the capacity of the class and available rooms, then held Multiple Intelligences Research (MIR). Teacher input; condition. The main thing is to be willing to continue to learn and be committed, a written test is carried out, practice (micro-teaching), and interviews. Learning process; Composing teacher lesson plan based on MIR and SOP results, implementing multiple strategies bits of intelligence based on how the brain works, and evaluate/assess competence students, accompanied by a consultant “Guardian Angel. Student output. Student outputs; student competencies include cognitive, psychomotor, and effective, which are assessed based on authentic assessment with the concept of ipsative-discovery ability. While teacher competence is assessed based on 4 components (student learning outcomes, lesson plan, creativity, and teacher behavior). Every semester students and teachers receive reports. The teacher's report card serves as a determinant of achievement resulting in an increase in salary and rank.